2021
DOI: 10.18176/jiaci.0633
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G4–Related Disease: What an Allergist Should Know

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 131 publications
(326 reference statements)
0
5
0
Order By: Relevance
“…IgG4-RD is featured by often elevated levels of serum IgG4 and IgE ( 24 26 ). In line with previous studies, our findings also showed that the concentrations of serum IgG4 and IgE were significantly increased in IgG4-RD patients compared with HCs.…”
Section: Discussionmentioning
confidence: 99%
“…IgG4-RD is featured by often elevated levels of serum IgG4 and IgE ( 24 26 ). In line with previous studies, our findings also showed that the concentrations of serum IgG4 and IgE were significantly increased in IgG4-RD patients compared with HCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the first cases were reported in Japan and other Asian countries, IgG-4-RD can affect all racial and ethnic groups even with a low reported prevalence. The mean onset age is 59 years, but some cases were described also in the paediatric population (Carballo et al, 2021). Most of the studies reported a slight male prevalence (around 56%), not always confirmed in most recent studies.…”
Section: Introductionmentioning
confidence: 90%
“…Another differential diagnosis of iMCD, especially of the plasma cell type, is IgG4-RD, which is a systemic inflammatory disorder characterized by sclerosing inflammation rich in IgG4-expressing plasma cells. This disease frequently affects the pancreas, salivary glands and lymph nodes, but it can involve almost any tissue [ 64–70 ]. Misdiagnosis may be due to the fact that iMCD patients may have an elevated serum IgG4 level, while some cases of IgG4-RD may show Castleman-like histopathology.…”
Section: Inflammatory Conditions That Resemble Clinical or Histopatho...mentioning
confidence: 99%